Solusi Pembelajaran Anak Usia Dini di Era Pandemi dengan Metode Pembelajaran berbasis Hiburan Edukasi (Current Research in Education: Conference Series Journal, 2022)
Covid-19 is declared a pandemic that has spread to all parts of the world. The spread is so fast that it takes the best effective way to prevent transmission. One way is to keep a distance in order to break the chain of transmission. The statement explains that not to cluster in one room, as in learning, namely by learning in the classroom. This has led to changes in learning nationally, emerging with the phrase